Expanding our understanding of backbone organizations in collective impact initiatives. Issue 3 (27th May 2018) - DuBow, Wendy; Hug, Sarah; Serafini, Brian; Litzler, Elizabeth
Abstract: This article explores the question of what mechanisms a backbone organization uses in a collective impact initiative to help diverse participants make organizational and social change. Qualitative data gathered from interviews with and observations of the participant organizations illustrate the ways that the backbone organization facilitated movement toward a common goal, making change. In this initiative, the participants were responsible for making their own organizational changes, which in turn, help to change the larger inequitable ecosystem. Data revealed five key mechanisms the backbone organization used to facilitate change-making among participating organizations: regular convenings, accountability, national visibility, top-level leader involvement, and coaching. These mechanisms helped participant organizations integrate new knowledge and implement multi-pronged, customized strategies to navigate systemic change together. Finally, four suggestions for intentional backbone facilitation are proposed to help strengthen collective impact initiatives.